A Generalization of Lacunary Equistatistical Convergence of Positive Linear Operators - Yusuf Kaya; Nazmiye Gönül (Abstract and Applied Analysis)
In this paper we consider some analogs of the Korovkin approximation theorem via lacunary equistatistical convergence. In particular we study lacunary equi-statistical convergence of approximating operators on spaces, the spaces of all real valued continuous functions dened on and satisfying some special conditions.